Clinical and pathological impact of VHL, PBRM1, BAP1, SETD2, KDM6A, and JARID1c in clear cell renal cell carcinoma. Issue 1 (29th October 2013) - Gossage, Lucy; Murtaza, Muhammed; Slatter, Andrew F.; Lichtenstein, Conrad P.; Warren, Anne; Haynes, Beverley; Marass, Francesco; Roberts, Ian; Shanahan, Susan J.; Claas, Andreas; Dunham, Andrew; May, Andrew P.; et al.
<x xml:space="preserve">Abstract</x> VHL is mutated in the majority of patients with clear cell renal cell carcinoma (ccRCC), with conflicting clinical relevance. Recent studies have identified recurrent mutations in histone modifying and chromatin remodeling genes, including BAP1, PBRM1, SETD2, KDM6A, and JARID1c. Current evidence suggests that BAP1 mutations are associated with aggressive disease. The clinical significance of the remaining genes is unknown. In this study, targeted sequencing of VHL and JARID1c (entire genes) and coding regions of BAP1, PBRM1, SETD2, and KDM6A was performed on 132 ccRCCs and matched normal tissues. Associations between mutations and clinical and pathological outcomes were interrogated. Inactivation of VHL (coding mutation or promoter methylation) was seen in 75% of ccRCCs. Somatic noncoding VHL alterations were identified in 29% of ccRCCs and may be associated with improved overall survival. BAP1 (11%), PBRM1 (33%), SETD2 (16%), JARID1c (4%), and KDM6A (3%) mutations were identified. BAP1‐mutated tumors were associated with metastatic disease at presentation (P = 0.023), advanced clinical stage (P = 0.042) and a trend towards shorter recurrence free survival (P = 0.059) when compared with tumors exclusively mutated for PBRM1. Our results support those of recent publications pointing towards a role for BAP1 and PBRM1 mutations in risk stratifying ccRCCs. Further investigation of noncoding alterations in VHL is warranted. © 2013 Wiley Periodicals, Inc.